Răspuns :
Răspuns:
[tex]102 - 72 \sqrt{2} [/tex]
Explicație pas cu pas:
[tex](4 \sqrt{2} - 6) {}^{2} + (3 \sqrt{2} - 4) {}^{2} =?[/tex]
[tex](4 \sqrt{2} - 6) {}^{2} = (4 \sqrt{2} ) {}^{2} - 2 \times 4 \sqrt{2} \times 6 + 6 {}^{2} = 32 - 48 \sqrt{2} + 36 \\ am \: folosit \: formula \: (a - b) {}^{2} = {a}^{2} - 2ab + {b}^{2} \: pentru \: a \: rezolva[/tex]
[tex]ne \: ramane \: 32 - 48 \sqrt{2} + 36 + 18 - 24 \sqrt{2} + 16\\ = 102 - 72 \sqrt{2} [/tex]
[tex](3 \sqrt{2} - 4) {}^{2} = (3 \sqrt{2} ) {}^{2} - 2 \times 3 \sqrt{2} \times 4 + {4}^{2} = 18 - 24 \sqrt{2} + 16 \\ am \: folosit \: formula \: (a - b) {}^{2} - 2ab + {b}^{2} pentru \: a \: rezolva[/tex]
Rezultatul este la mijloc, asa s a scris, nu stiu de ce !!